STORIES THAT STILL MATTER: REFLECTIONS ON STUDYING LITERATURE AMID DIGITAL NOISE - Susanne Sitohang (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2025)
There appears to be a steady decline in interest in literary studies, as seen in the significant drop in new student enrollment in the English Literature Study Program at the Fakultas Sastra dan Bahasa, Universitas Kristen Indonesia (FSB-UKI) —from 70 students in 2021 to only 25 in both 2023 and 2024. This trend raises important questions: Why are fewer prospective students choosing literature as their major? What factors influence this shift? Rather than solely speculating on the external, this study turns inward to reflect on what is already happening within the program. It seeks to understand how current students perceive the experience of studying literature in today’s globalized and digitally driven world. The study focuses on three key areas: what students think about the value of literature today, how their views have changed since joining the program, and which parts of their learning feel most meaningful or need improvement. Furthermore, the research aims to ask a deeper and more important question: Is literature still relevant today? If so, as teachers of literature, we need to ask how we can make literature engaging and meaningful again for our younger generations who are now growing up in a digital world. The results of this research will be beneficial not only as a reflection but also as an evaluation tool for the program itself—informing efforts to create a more relevant, dynamic, and engaging literature curriculum that meets the needs of today’s learners while honoring the discipline’s rich cultural and humanistic traditions. In exploring the students’ views, this research makes use of a bilingual open-ended questionnaire to be filled out by students currently studying at the English Literature Study Program at FSB-UKI. By centering student perspectives, this study contributes not only to internal curriculum reflection but also to broader conversations about the future of literary education and its place in shaping cultural and human values in contemporary Indonesia.